2006
DOI: 10.1007/s00125-006-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and risk of bladder cancer: a meta-analysis

Abstract: Aims/hypothesis Epidemiological evidence indicates that individuals with diabetes mellitus have an increased risk of several cancers. We performed a systematic review with meta-analysis to evaluate the association between diabetes and risk of bladder cancer. Methods Pertinent studies were identified by searching MEDLINE (from January 1966 to July 2006) and by reviewing the reference lists of retrieved articles. We included case-control and cohort studies reporting relative risk (RR) estimates with 95% CIs (or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
196
5
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(219 citation statements)
references
References 44 publications
(50 reference statements)
14
196
5
3
Order By: Relevance
“…Our lower estimates relative to this study may be attributed to the use of national population rates as the comparator (rather than a nondiabetic population). SIR estimates for type 2 diabetes obtained in our study are also comparable to previous meta-analyses performed on sitespecific cancer incidence (4,(14)(15)(16)(17)(18)(19)(20). We add to the current literature around type 2 diabetes and cancer incidence more precise risk estimates for some of the less common cancers.…”
Section: Comparison With the Literaturesupporting
confidence: 75%
“…Our lower estimates relative to this study may be attributed to the use of national population rates as the comparator (rather than a nondiabetic population). SIR estimates for type 2 diabetes obtained in our study are also comparable to previous meta-analyses performed on sitespecific cancer incidence (4,(14)(15)(16)(17)(18)(19)(20). We add to the current literature around type 2 diabetes and cancer incidence more precise risk estimates for some of the less common cancers.…”
Section: Comparison With the Literaturesupporting
confidence: 75%
“…There is substantial evidence indicating that patients with type 2 diabetes have an increased risk of cancer and cancer mortality [1][2][3][4][5][6]. The relationship between type 2 diabetes and various forms of cancer is biologically plausible, with insulin resistance, hyperinsulinaemia and elevated levels of IGF-1 in patients with type 2 diabetes involved in promotion of tumour cell growth [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous epidemiological studies have identified associations between diabetes and several types of cancer in various populations [9][10][11][12][13][14][15][16][17][18][19] (Table 2). While the literature indicates a strong and consistent increased risk of cancer in people with type 2 diabetes, the strength of association depends on the specific cancer site.…”
Section: Epidemiology Of Diabetes and Cancer Incidencementioning
confidence: 99%